Pengembangan Media Pembelajaran Berbasis Android Untuk Penumbuhan Literasi Sains Siswa Pada Materi Sistem Periodik Unsur - Kusumawardhani, Ria; Suryati, Suryati; Khery, Yusran (Hydrogen: Jurnal Kependidikan Kimia, 2019)
The aims of this study were to produce android base learning media in elements periodic system subject material and to evaluate its eligibility, pratical, and effectiveness to grow student science litaracy. In form of Research and Development, this study was carried out by ADDIE Model (Analysis, Design, Development, Implementation and evaluation). Data was collected by respons questionnaire, validaty questionnaire and science literacy test. Data was analyzed by eligiblepercentage, eligible categorization, and N-gain test. Study result showed that content validity and media design validity was very eleigible with 81.11% and 83.97% of eligibility respectively. Practicioner and student respon was very eligible with 80.95 % and 89.02 % of eligibility respectively. Effectivity trial obtained 0.62 of N-gain with moderate category. It can be concluded that android base learning media was very eligible to applied for students science literacy growth on elements periodic system learning effectively.